Strategi Pemasaran RR Outdoor Purworejo Periode 2021-2022 - Susbiyanto, Rahmat; Hidayati, Aprihatiningrum (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
RR Outdoor Purworejo, as a commercial company engaged in outdoor equipment rental services to take advantage of the existing potential, must be very intense in paying attention to the promotion side of the company. So the researchers conducted this research with the aim of formulating the marketing strategy of the RR Outdoor Purworejo company for the period 2021-2022. This study uses a 3c analysis approach which includes: customers, companies, and competitors by using a quantitative, qualitative research approach with survey methods that include questionnaire research instruments and interviews with <50 respondents involved. The results of this study directed RR Outdoor Purworejo to formulate its marketing strategy for the period 2021-2022, namely the Tour Guide promo program for fun camping, open trips, and private trips.